1982
DOI: 10.2172/5260598
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the solid, airborne materials created by the interaction of UF/sub 6/ with atmospheric moisture in a contained volume

Abstract: DISCLAIMERNeither the United Stater GAvernment nor any agency Ihereoi. rior any Of their employees. makesmy warranty. expiell 01 8mp18ed. or afsumei any legal liability or responribiliry for the ~C C U~C Y .ComDleteness. or urefulnerr of any !nformation. apparatus. product. or Process dizlared. or leOrelenfl thk.#tr 11% nauld no7 lnfrlnge pl8vately owned rlghts. Reference herein to any IpeClflC mmmercisl product. process. or S~Y I C B by trade name. Iraderrurk. manufacturer. or otherwise. does not necer~rtlv m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…UF 6 is a very reactive gas that reacts with atmospheric moisture to form uranium oxyuoride (UO 2 F 2 ). 7,8 Given the large amounts of UF 4 and UF 6 used at conversion and enrichment facilities, very small releases to the atmosphere are common and result in the deposition of particulate UF 4 and/or UO 2 F 2 material. So, the detection of a signicant amount of F in such U particles is a proof that uranium has been converted at one point before the sampling.…”
Section: Introductionmentioning
confidence: 99%
“…UF 6 is a very reactive gas that reacts with atmospheric moisture to form uranium oxyuoride (UO 2 F 2 ). 7,8 Given the large amounts of UF 4 and UF 6 used at conversion and enrichment facilities, very small releases to the atmosphere are common and result in the deposition of particulate UF 4 and/or UO 2 F 2 material. So, the detection of a signicant amount of F in such U particles is a proof that uranium has been converted at one point before the sampling.…”
Section: Introductionmentioning
confidence: 99%
“…104,105 Two early studies considering the particle size and morphology of the UO 2 F 2 particulate, conducted by Pickrell and by Lux, yielded somewhat contrasting findings. 106,107 Pickrell concluded that the RH and aerosol incubation period, or growth time, affected the particle size and morphology of the resulting UO 2 F 2 particulate, whereas Lux found the particle size distribution of the UO 2 F 2 particulate matter to be largely unaffected by varying humidity. To help resolve this disagreement, recent work by Kips et al used SEM to study the effect of humidity on the UO 2 F 2 particle morphology.…”
Section: Rolison Et Al and Migeon Et Al Recently Investigated The Mol...mentioning
confidence: 99%
“…The white fog is an aerosol consisting of particulate matter or particles of complicated chemical composition. After extensive characterization efforts for the particulate materials in the past few decades, we now know that the aerosol population consists of UO2F2 as a main reaction product when UF6 is in contact with H2O vapor (Kessie 1967, Bostick et al 1983, 1984, Kips et al 2007, Kips and Kristo 2009, Pickrell 1982, 1984, 1985. UF6 hydrolysis produces solid UO2F2 particles and also HF, a hazardous toxic gas, as written in Eq.…”
Section: Pathways To Airborne Uranyl Particlesmentioning
confidence: 99%
“…Previous microscopic studies of UO2F2 formation produced many micrographs (Bostick et al 1983, 1984, Kips et al 2007, Pickrell 1982, 1984, 1985. As the UO2F2 particles were produced, they were likely to be in a spherical shape at the beginning.…”
Section: Size Of Primary Particlementioning
confidence: 99%